Slight Progress Wrong Direction of Agricultural Development: Analysis of Agricultural Census 2013 - Agusta, Ivanovich (Journal of Rural Indonesia, 2013)
Agricultural Census 2013 shows agricultural sector as a provider of food, as well as livelihoods of majority of Indonesian people. The various agricultural sub-sectors develop mainly in Java and Bali, particularly food crops, horticulture, plantation, and animal husbandries. Most of the agricultural processing and services are also concentrated here. Social exclusion of smallholder households, as well as centralizing control of big land, are simultaneously happened, also lowest layers of the ruler of the land of the most marginalized. Meanwhile, about 45 percent of land (0.5-30 hectares) are owned by only 11 percent of affluent households. Clearly agricultural development trajectory for peasant is still far away to reach. © 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keyword:  agrarian, agricultural development, agricultural sector, smallholdersReceived: 23th October 2013; Accepted: 19th November 2013[How to Cite: Agusta, I. (2013). Slight Progress: Wrong Direction of Agricultural Development Analysis of Agricultural Census 2013. Journal Of Rural Indonesia, 1(1), 15-34. Retrieved from http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/71]